Early readers: three read along stories - Davies, Gill (Brown Watson England, 2010)
An *Early Readers Book* is designed to help young children develop their reading skills with simple language, short sentences, and engaging illustrations. These books are perfect for beginners, offering a fun and supportive introduction to reading while building confidence and vocabulary.